Sharia Cooperative Compliance Analysis of Mujur Aceh Sharia Financing Saving and Loan Cooperative - Saputra, Edy; Koesmawan, Koesmawan (Al-'Adl, 2024)
This research aims to assess the compatibility of contracts, Standard Operating Procedures (SOPs), and marketing materials used by KSPPS Mujur with Sharia principles. KSPPS Mujur transitioned to the Sharia system following the implementation of Qanun LKS but has yet to establish an active Sharia Supervisory Board. The research method employed is Critical Analysis, which is a descriptive method enriched with critical analysis based on Sharia principles and Sharia oversight theory as an additional reference. The research findings indicate that the contracts, SOPs, and marketing materials of KSPPS Mujur do not meet Sharia standards. The implications of this research include the importance of Sharia oversight and the establishment of Sharia Boards at the district/city level in Aceh, the need for document revisions to align with Sharia principles, and serving as a foundation for further research contributing to the development of Islamic financial institutions.